Preparation and catalytic activity of bone-char ash decorated with MgO - FeNO(3) for ozonation of reactive black 5 dye from aqueous solution: Taguchi optimization data - Asgari, Ghorban (Data Brief, 2017)
Reactive dye is one of the most applicable dyes in textile industries which its release to the water bodies creates a concern for environmentalists. Here, in this data article a bone-char (BC) ash decorated with MgO-FeNO(3) for removing reactive black 5 (RB5) dye in a catalytic ozonation process (COP) system. Operational parameters data such as initial RB5 concentration, pH, catalyst dosage, and reaction time were optimized using Taguchi method. The optimal conditions for initial RB5 concentration, pH, catalyst dosage, and reaction time were determined 10 mg/L, 10, 0.1 g/L, and 15 min, respectively. Data of Taguchi optimization tests indicated that the initial RB5 concentration had a significant influence on RB5 removal efficiency (54.03%) during the catalytic ozonation process, and reaction time had lower contribution (2.04%).